THE EFFECT OF GENRE-BASED APPROACH AND LEARNER AUTONOMY ON THE WRITING COMPETENCE OF THE EIGHTH GRADE STUDENTS OF SMP HARAPAN NUSANTARA - Artini, N. M. S.; Seken, I K.; Budasi, I G. (Universitas Pendidikan Ganesha, 2019)
This study aimed at: a) finding out whether or not there is a significant difference in writing competence between the students who were taught by using genre based approach and those who were taught by using a conventional strategy; b) finding out whether or not there is an effect of the interaction between the implementation of genre based approach and learner autonomy on the students writing competence; 3) finding out whether or not there is a significant difference in writing competence between the students with high autonomy treated by using genre based approach and those treated by using a conventional strategy; 4) finding out whether or not there is a significant difference in writing competence between the students with how autonomy who were treated by using genre based approach and those treated by using a conventional strategy. The study employed a post test for control group and an experiment group with 2 x 2 factorial designs. The population of the study was 196 eighth grade students of SMP Harapan Nusantara in academic year 2015/2016 where 144 of them were selected as the sample of the study through cluster random sampling technique. The data were collected by means of attitude questionnaire and writing competence test and were analyzed by using Two-Way ANOVA and Tukey test. The result of this research showed that: a) there was significant difference in writing competence between the students who are taught by using genre based approach and those who are taught by using a conventional strategy, b) there was significant effect of the interaction between the implementation of genre based approach and learner autonomy on the students’ writing competence, c) there was significant difference in writing competence between the students with high autonomy treated by using genre based approach and those treated by using a conventional strategy and d) there was significant difference in writing competence between the students with low autonomy who are treated by using genre based approach and those treated by using a conventional strategy. The implication of this study reveals that a Genre-Based Approach is useful approach for supporting students’ development.